Uji Efek Penurunan Glukosa Darah Dapagliflozin Monoterapi Dan Kombinasi Dengan Glucose Lowering Agent Lainnya - Almas Amalul Fasha; Ikhwan Yuda Kusuma; Galih Samodra (Pharmacon: Jurnal Farmasi Indonesia, 2021)
The success of DM therapy with antidiabetic drug monotherapy is about 25-50% effectiveness, therefore combination therapy is needed. Inhibitor sodium glucose co-transporter 2 (SGLT-2) is a new anti-diabetic drug intended for personal therapy of patients with type 2 diabetes. SGLT2 inhibitors work by inhibiting glucose reabsorption in the proximal tubule so that glucose will be excreted with urine. SGLT-2 besides being used as monotherapy can also be combined with other DM drugs.  This study aimed to determine the effectiveness of dapagliflozin monotherapy compared to metformin, saxagliptin and glimepiride in alloxan-induced Balb-c strain mice. This research was conducted experimentally on alloxan-induced hyperglycemic mice and the treatment was given for 7 days. The treatment groups were: I. normal, II. alloxan, III. dapagliflozin (D) and the dapagliflozin combination group with: IV. Metformin (DM), V. saxagliptin (DS), VI. Glimepiride (DG), VII. saxagliptin + metformin (DSM). Analysis of the decrease in blood sugar compared between groups on the 7th day after administration. The analysis was carried out using ANOVA test with a 95% confidence level. The results of this study indicate that all treatments with antidiabetic drugs alone or in combination given for 7 days can control blood sugar levels to 120 mg/dL. The combination of dapaglyfozine (DM, DS, DSM) showed a significant difference with groups D and DG (p0.05). The combination of dapagliflozin with Metformin, Saxagliptin and Meformin+Sazagliptin showed a good effectiveness in lowering blood sugar levels compared to other combinations and alone.